Care and Support Services for the Elderly in the City of Vienna and the Vienna Social Fund - Yaşar Tınar (Sosyal Siyaset Konferansları Dergisi)
From the very beginning of history, many people need help. During the assessment, the priority is to care for the elderly population who need help. Therefore, while services for the elderly (assistance, care, etc.) were provided by the family, which was one of the actors of social policy in the first periods of history, today services for the elderly are provided by the state, local governments and the private sector in a more institutional way, together with the family. Especially after the industrial revolution, the role and function of local governments in aid and care has gained importance due to the excessive immigration of cities, the increase in population and the increase in social demands and needs. This study aimed to present the services available for elderly residents in Vienna and Europe. The results of this study can be used as a basis for studies considering the elderly population. The study setting should have the highest number of Austrians. Therefore, the city of Vienna was accepted as the study sample. In addition to all other services, the Vienna Social Fund is a social service education provider in Vienna, which focused on the care of the elderly dwelling in institutions.